Modifiable risk factor score and fecundability in a preconception cohort in Singapore - Loy, See Ling (2023)
Although multiple modifiable risk factors have been identified for reduced fecundability (defined as lower probability of conception within a menstrual cycle), no scoring system has been established to systematically evaluate fecundability among females who are attempting to conceive.